2019
DOI: 10.3389/fpls.2019.00374
|View full text |Cite
|
Sign up to set email alerts
|

The Phytophthora RXLR Effector Avrblb2 Modulates Plant Immunity by Interfering With Ca2+ Signaling Pathway

Abstract: In plants, subcellular fluctuations in Ca 2+ ion concentration are among the earliest responses to biotic and abiotic stresses. Calmodulin, which is a ubiquitous Ca 2+ ion sensor in eukaryotes, plays a major role in translating these Ca 2+ signatures to cellular responses by interacting with numerous proteins located in plasma membranes, cytoplasm, organelles and nuclei. In this report, we show that one of the Phytophthora … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 61 publications
0
25
0
Order By: Relevance
“…SFI8/Avrblb2 is a core P. infestans RXLR effector, found to have multiple host targets associated with diverse defense mechanisms. In addition to targeting MAPK signaling, SFI8/Avrblb2 and its other homologs interact with diverse calmodulins (CaMs) (Naveed et al, 2019). CaMs are ubiquitous Ca 2+ sensors in eukaryotes that play a major role in calcium signaling by interacting with numerous downstream targets.…”
Section: Modulation Of Mapk and Calcium Signaling Pathways By Rxlr Efmentioning
confidence: 99%
“…SFI8/Avrblb2 is a core P. infestans RXLR effector, found to have multiple host targets associated with diverse defense mechanisms. In addition to targeting MAPK signaling, SFI8/Avrblb2 and its other homologs interact with diverse calmodulins (CaMs) (Naveed et al, 2019). CaMs are ubiquitous Ca 2+ sensors in eukaryotes that play a major role in calcium signaling by interacting with numerous downstream targets.…”
Section: Modulation Of Mapk and Calcium Signaling Pathways By Rxlr Efmentioning
confidence: 99%
“…our data also indicate that upon the activation of Ca 2+ influx, multiple Ca 2+ sensors may participate in the coordinated transmission of Ca 2+ -signaling, since CaCDPK15, CaCBL1 and CaCML13 are all participate in the pepper defense-signaling against R. solanacearum infection. This arrangement may make the immune-signaling less sensitive to the attacks of pathogen derived effectors, once per component is destroyed by pathogens, it may be compensated on time by other components, since components in Ca 2+ -signaling such as calmodulin may be target of pathogen derived effectors [12,13]. Another biologic importance of the involvement of multiple-signaling components in defense-signaling is that it can provide great regulatory potential for the feasible response of plants to different environmental conditions, since different signaling components can be modulated by internal or external stimulus.…”
Section: Discussionmentioning
confidence: 99%
“…Csa2G007990 encodes calmodulin and is highly expressed in cucumber. Naveed et al (2019) found that when calmodulin bound to the effector peptide protein Avrblb2, it incited a hypersensitive response. Csa2G009430 encodes a transmembrane protein that has been widely studied in animal disease resistance, but not in plants.…”
Section: Discussionmentioning
confidence: 99%